The Geometric Design of New Jakarta-Cikampek Highway Access Using Autocad® Civil 3D: A Case of West Karawang Industrial Area - Aditya Hakim Agniya; Andri Irfan Rifai; Mohamad Taufik (Indonesian Journal of Multidisciplinary Science, 2022)
Along with the development of the industrial sector in Indonesia, Karawang has excellent opportunities and potential to develop in this field, where Karawang currently has congestion problems from and towards industrial estates in a certain period. The geometric planning of the access road to the Jakarta-Cikampek Toll Road aims to provide references and preliminary designs to unravel the congestion problem. Systematic calculations and integrated visual depictions of AutoCAD Civil 3D® software assist the geometric design process of such roads. The research method used is quantitative. The necessary data sources are obtained from observation methods, literature studies, and primary data. Planning begins with determining the design criteria of the purpose and the function of such roads. Then the design criteria are used as a reference to determine variables in horizontal and vertical paragraphs. From the results of horizontal paragraph planning, one arc of FS (Full Circle) and 2 SCS (Spiral-Circle-Spiral) were obtained. Then the results of the vertical paragraph design got two concave arches.